Determinants of Healthcare Expenditure: A Cross-Sectional Analysis at the Country Level - Malinowski, Piotr (Journal of Education, Health and Sport, 2024)
This study examines the determinants of healthcare expenditure through a cross-sectional analysis of 153 countries using 2018 data. The research employs a classical linear regression model to identify key socioeconomic and demographic factors influencing healthcare spending per capita, expressed in PPP (Purchasing Power Parity). The results show that GDP per capita, public health expenditure as a percentage of GDP, physician availability, and out-of-pocket healthcare costs are statistically significant determinants of healthcare spending. Specifically, the analysis highlights the non-linear relationship between GDP and healthcare expenditure, where wealthier nations tend to spend disproportionately more on healthcare. Public investment in healthcare and the availability of medical professionals also play crucial roles in shaping national healthcare expenditures. Out-of-pocket expenses by households further increase overall healthcare costs, especially in countries with lower public funding. The proposed model explains 96.5% of the variation in healthcare expenditure, suggesting that the selected variables are strong predictors of healthcare spending. These findings provide valuable insights for policymakers, particularly in the context of balancing public healthcare financing and improving access to medical services while managing overall costs.